The influence of Islamic religiosity on e-book piracy: an accounting student perspective - Dela Anggraeni; Muamar Nur Kholid (Faculty of Business & Economics, Universitas Islam Indonesia, 2020)
Purpose: This study aims to examine the determinant factors affecting accounting student’s intention to carrying out e-book piracy.Methodology: This study used quantitative method with primary data through questionnaire from 187 selected students as samples. The data were analyzed using the PLS SEM supported by SmartPLS software.Findings: The findings of the analysis showed that attitude significantly affects the intention of carrying out E-book piracy while Islamic religiosity negatively influences the intention of carrying out E-book piracy. The findings of this study contribute to the literature regarding piracy in general and e-book piracy in particular.Practical implications: The present study also has implications for higher education institution especially for accounting study program to formulate strategies to minimize e-book piracy by accounting studentsOriginality: This study integrates Islamic religiosity in a research model which is rarely done in the context of research on e-book piracy by accounting students